ESG and Capital Structure: A Moderation Analysis of Firm Size - Yenny Wati; Achmad Tavip Junaedi; Harry Patuan Panjaitan; Nyoto Nyoto; Astri Ayu Purwati (Fakultas Ekonomi dan Bisnis, Universitas Muhammadiyah Cirebon, 2025)
Main Purpose - This study aims to determine the effect of ESG practices on a firm's capital structure, using firm size as a moderating variable.Method - This study utilizes moderated regression analysis conducted with Eviews. The research sample included businesses listed on the Indonesia Stock Exchange's IDXESGL index between 2020 and 2023.Main Findings - Companies with higher ESG scores typically have lower debt-to-asset and debt-to-equity ratios. Firm size can influence the relationship between ESG and capital structure. The relationship between ESG and capital structure has piqued the interest of investors and other stakeholders that can influence corporate decisions regarding debt and equity composition.Theory and Practical Implications - Companies increasingly recognize that sustainable business practices are not only ethically responsible but also financially profitable. Research can provide more precise policy suggestions to assist businesses in embracing strong ESG practices and enhancing their access to funding.Novelty - This study examines companies listed in Indonesia's ESG index, making the research findings more relevant to the local context, with firm size as a moderating variable.